High-flow nasal cannula oxygen therapy: more than a higher amount of oxygen delivery - Maury, Eric; Alves, Mikael; Bigé, Naike (Journal of Thoracic Disease, 2016)
The process of disconnecting critically ill patients from the respirator is a crucial step of patients care (1). Weaning can be initiated when stable patients have recovered enough to tolerate a spontaneous breathing trial (SBT). This requires daily identification of patients with an acceptable P/F ratio obtained with no more than 40–50% of inspiratory of oxygen, a low level of PEP (no more than 5 cm of water), hemodynamic stability (no or minimal regimen of intravenous vasopressors, no more than 5 µg/kg/min of dobutamine), and a neurologic status likely to allow spontaneous breathing (no or minimal sedation, ability to cough, absence of copious secretion) (2,3). The necessity to start SBT only in patients with a low temperature (